Symposium 13: Identity Construction and Dialogue Genres – How Notions of Dialogue May Influence Social Presence in Networked Learning Environments - Gustafson, Jenny; Hodgson, Vivien; Tickner, Sue (Proceedings of the International Conference on Networked Learning, 2004)
When analysing networked learning environments, researchers commonly try to explain the variation in activity, collaboration and learning outcomes by focusing on characteristics of the environment that primarily concern design and functionality. We want to draw attention to other aspects that affect networked learning, that concern how participants engage in dialogue and what consequences notions of dialogue may have on collaboration and learning. Building on theories of social presence and discourse analysis, we show how online identities are formed and explain how these influence the conditions for learning in networked-based environments. The paper is primarily intended for researchers in networked learning, but is also relevant for practitioners in the field, for example people involved in teaching or monitoring network-based courses, who want to know more about how group dynamics can be affected by what is going on in the dialogue between the participants.